A Grammar of the Eastern European Hasidic Hebrew Tale - Kahn, L. (Studies in Semitic Languages and Linguistics, 2015)
This volume constitutes the first reference grammar of the Hasidic Hebrew hagiographic tales composed in late nineteenth- and early twentieth-century Eastern Europe. It presents a thorough survey of Hasidic Hebrew orthography, morphology, syntax, and lexis illustrated with extensive examples.